Mandibular First Molar with a Radix Entomolaris: An Endodontic Dilemma - Sarangi, Priyanka (Tehran University of Medical Sciences, 2014)
It is known that the mandibular first molar can display significant anatomical variations namely the number of root canals, the number of roots and morphology. Mandibular molars may sometimes have an additional root located lingually (the radix entomolaris) or buccally (the radix paramolaris). If encountered, an awareness and understanding of this unusual root and its canal morphology can contribute to the successful outcome of root canal treatment. This case report discusses endodontic treatment of a mandibular first molar with a radix entomolaris, which is a rare entity and poses as an endodontic dilemma for the clinician with respect to diagnosis and subsequent treatment. Clinicians should be aware of these unusual root morphologies in the mandibular first molar which needs strategic treatment as unfilled canals remain a nidus for infection and can compromise treatment outcome.